Bandwidth Shaping Menggunakan Proxy Squid - Dwi Yatmoko Siambudi; wamiliana .; wisnu wardhana (Universitas Lampung, 2018)
The development of technology is very fast. Nowadays, technology has influenced human life. For most people, handphone and computer now become a necessity. Computer can give information as we need with internet, but internet can cause a negative influence as well. In this research, we build an web base application which can block a negative-influence sites using Squid Proxy. Squid is a daemon that used as a proxy server and web cache. It can work as a connection sharing, filtering and caching. The web which domain block is successfully built which can create a bandwidth share and domain block web base application.